Letter: sprue‐like enteropathy associated with angiotensin II receptor blockers other than olmesartan. Issue 4 (14th July 2017) - Zanelli, M.; Negro, A.; Santi, R.; Bisagni, A.; Ragazzi, M.; Ascani, S.; De Marco, L.
Abstract : Linked Content This article is linked to Zanelli and Negro et al and Marthey and Carbonnel papers. To view these articles visithttps://doi.org/10.1111/apt.14176 andhttps://doi.org/10.1111/apt.14191 .